(untitled) (Journal of the College of Basic Education, 2022)
Wavelets methods are commonly used for the numerical solution of partial differential equations. In this paper, we extend the Legendre wavelet polynomial of one variable to Legendre wavelet polynomial of two variables to approximate the solution of fractional partial differential equations. Convergence analysis for the solution is discussed. Total error is computed for the numerical examples to demonstrate the validity of the method